Nickel‐Catalyzed Stereo‐ and Enantioselective Cross‐Coupling of gem‐Difluoroalkenes with Carbon Electrophiles by C−F Bond Activation. Issue 6 (23rd December 2021) - Zhu, Ziqi; Lin, Lin; Xiao, Jieshuai; Shi, Zhuangzhi
Abstract: Stereo‐ and enantioselective cross‐electrophile coupling involving C−F bond activation is reported. Treatment of gem‐difluoroalkenes with racemic benzyl electrophiles in the presence of a chiral nickel complex using B2 pin2 as a stoichiometric reductant allows the construction of a C(sp 2 )−C(sp 3 ) bond under mild conditions, affording a broad range of monofluoroalkenes bearing stereogenic allylic centers. Initial mechanistic studies indicate that a radical chain pathway may be operating, wherein the ester group in the gem‐difluoroalkene promotes C−F bond activation through oxidative addition to a Ni species . Abstract : A cross‐electrophile coupling between gem ‐difluoroalkenes and benzyl electrophiles proceeds through nickel‐catalyzed chelation‐assisted C−F bond activation and shows excellent stereoselectivity and enantioselectivity.